Method for manufacturing biological matrix for wheat - CHEN WEI (2014)
The invention discloses a method for manufacturing a biological matrix for wheat. The method comprises the following steps: crushing wheat straw, corn straw and pumice stones, adding water to the crushed wheat straw, corn straw and pumice stones, and mixing with turf and fermentation bed packing and adding a small quantity of aged matrixes to prepare into a fermentation matrix; stacking, decomposing and regularly overturning the mixed fermentation matrix to complete composting, and then introducing earthworms into a compost; aging, and carrying out quality inspection on the compost after the aging is completed; drying the qualified compost, and crushing to prepare a finished product. By adopting the mode, the method for manufacturing the biological matrix for the wheat has the advantages of wide material source, low cost, stability and thoroughness in decomposition, no environmental pollution, less peculiar smell, high fertility, good application effect, easiness for manufacturing and the like.